2022
DOI: 10.1186/s13018-022-03249-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the safety and efficacy of unilateral biportal endoscopic lumbar interbody fusion and uniportal endoscopic lumbar interbody fusion: a 1-year follow-up

Abstract: Objectives To compare the short-term outcomes of unilateral biportal endoscopic lumbar interbody fusion (BLIF) and uniportal endoscopic lumbar interbody fusion (ULIF). Methods Sixty patients diagnosed with L4/5 spinal stenosis who underwent BLIF and ULIF were included (30 in each group). Clinical evaluation was performed preoperatively and postoperatively in the 1st week, 1st month, and 1st year. Factors such as the visual analogue score (VAS), Osw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Then, an ELIF was performed using a lordotic polyetheretherketone (PEEK) graft (26 mm length × 10 mm width × 10 mm height) packed with allograft bone. The procedure was in line with the article we published earlier [ 7 ]. The surgery went smoothly in all steps including pedicle screws placement, decompression and cage implantation.…”
Section: Case Presentationmentioning
confidence: 68%
“…Then, an ELIF was performed using a lordotic polyetheretherketone (PEEK) graft (26 mm length × 10 mm width × 10 mm height) packed with allograft bone. The procedure was in line with the article we published earlier [ 7 ]. The surgery went smoothly in all steps including pedicle screws placement, decompression and cage implantation.…”
Section: Case Presentationmentioning
confidence: 68%
“…The UBE technique allows the establishment of portals through the skin without the limitation of operating a trocar, meanwhile, ULIF can place a larger cage and adjust the cage angle more conveniently, which may be the reason why ULIF has better fusion rate [ 16 ]. Previous studies have shown that ULIF presents the advantages of less trauma, less bleeding, faster postoperative recovery, and favorable fusion rate [ 5 ]. A meta-analysis by Yu et al [ 17 ] indicated that compared to conventional TLIF, ULIF has the advantages in relieving postoperative pain, shortening hospital stay, and enhancing functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Since Heo applied the UBE technique to transforaminal lumbar interbody fusion (TLIF) for the first time and got satisfactory outcomes in 2017 [ 4 ], the indications for UBE have gradually expanded to various degenerative spinal diseases. Studies have demonstrated that ULIF has shown favorable clinical outcomes in the treatment of lumbar degenerative diseases [ 5 ]. However, ULIF remains challenging in its early implementation.…”
Section: Introductionmentioning
confidence: 99%
“…After this, fixation of 4 percutaneous pedicle screws was done under C-arm guidance (Figure 2L and 2M). 13,[15][16][17]…”
Section: Surgical Technique Ubeifmentioning
confidence: 99%